The Impact of Furniture Layout on the Architectural Experience of Visitors at Pet Cafés - Airin Dian Nagari; Budi Sudarwanto; Siti Rukayah; Agung Budi Sardjono (Eduvest - Journal of Universal Studies, 2026)
Public spaces and quasi-public spaces such as cafes serve not only as places of consumption, but also as spaces for social experience, interaction, and relaxation. This study analyzed the influence of furniture layout on the architectural experience of visitors at Lamiao Cat Café as a quasi-public space. The method used was qualitative research with an observational approach through behavior mapping techniques, including person-centered mapping and place-centered mapping. This approach is employed to examine the relationship between spatial configuration, visitor behavior patterns, and the spatial experience formed. The results show that furniture layout affects circulation patterns, intensity of space use, and visitor comfort levels. Architectural experiences are formed in layers and sequentially, ranging from perceptual experiences through spatial readability and orientation, bodily and movement experiences through ease of circulation, to emotional experiences related to comfort and privacy. The accumulation of these experiences shapes the meaning of space for visitors. This study confirms that furniture layout functions as a guide to architectural experience, not merely as a functional element of space